Pattern Matching of Gene Sequencing Using LCS and String-Matching Algorithms - Nath, Ravindra; Srivastava, Prashant; Mall, Shachi (2025 3rd International Conference on Communication, Security, and Artificial Intelligence (ICCSAI), 2025)
In the field of medical sciene observe that the role of pattern matching in different kind of DNA structures are followed. Function and structure relationships between biological sequences call gene sequence can be based on sequence similarity. Pattern matching algorithm always played important role in Intrusion detection, information retrieval, computer virus signature match etc. To find these similarities the researchers are trying to aware people of similarity on the biological sequences. In today world, the biological sequence ie. gene sequence is an essential subject which bring insight into the new development and genetic relation between the genes. In this paper, we will explore the current state of the art of different string-matching algorithms like LCA to know and observe their time and space complexity. To perform this research, we measure the performance level of many algorithms with biological sequences.